2011
DOI: 10.1080/22311866.2011.10719094
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Antimicrobial, Antioxidant and Anticancer Activity of Leaves ofSyzygium benthamianum(Wight ex Duthie) Gamble

Abstract: The study was carried out on antimicrobial, antioxidant and anticancer activity of Syzygium benthamianum leaf extract. Chemical compositions of the leaf were analysed using GC/MS technique. A total of 24 compounds were identified among which 4-(4-ethylcyclohexyl)-1-pentyl-Cyclohexene (24.07 %) and Linoleic acid (15.16 %) are the major constituents. Antimicrobial activity of the leaf was observed on six bacterial and three fungal species, whose MIC values ranged from 100 to 500 μg/ml. At higher concentration, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Sesquiterpenoids are the major group of antioxidant in the ethyl acetate 34 . The activity of this extract is comparable with that of S. cumini 35 and S. aromaticum 11 and also has comparatively reduced activity with that of Syzygium benthamianum 36 . The effect of extract on Hep2 cell viability has been evaluated by MTT assay (Table 5).…”
Section: Resultsmentioning
confidence: 49%
See 1 more Smart Citation
“…Sesquiterpenoids are the major group of antioxidant in the ethyl acetate 34 . The activity of this extract is comparable with that of S. cumini 35 and S. aromaticum 11 and also has comparatively reduced activity with that of Syzygium benthamianum 36 . The effect of extract on Hep2 cell viability has been evaluated by MTT assay (Table 5).…”
Section: Resultsmentioning
confidence: 49%
“…The ethyl acetate extract of S. calophyllifolium exhibited higher activity compared to the activity of Jamun fruit extract (Eugenia jambolana) on breast cancer cells 37 and S. cumini on AML cells 35 and human cervical carcinoma cell lines (HeLa and SiHa) 38 . Even the viability percentage of Hep2 cell lines were less against S. calophyllifolium compared to S. benthamianum 36 and S. caryophyllatum 39 .…”
Section: Resultsmentioning
confidence: 85%
“…Myrtaceae Leaves Perennial Diarrhoea, dysentery (Nadkarni 1976), strengthening the teeth (Kirtikar and Basu 1999) Antihyperglycemic effect (Teixeira et al 1989), Antioxidant activity (Eshwarappa et al 2014), Antimicrobial, Antioxidant, Anticancer Activity (Kiruthiga et al 2011), Anti-inflammatory (Roy et al 2011), anti-allergic activity (Brito et al 2007) 18 Pui (Soraya et al 2015); anticancer activity (Kowsalya et al 2015); Antidiabetic activity (Jarald et al 2008); Diuretic Activity (Aruna et al 2013);Antiarthritic activity (Bhangale and Acharya 2014); anticonvulsive property (Odenigbo and Awachie 1993) (Shen et al 1988) (Subramanian and et al 1986) (Najafi et al 2009) (Najafi et al 2007), Antiulcer activity (Patil et al 2003a) 21 Koliyar Anti-Inflammatory Activity (Maity et al 1998) (Jain and Patil 2010), AntiProliferative Activity (Rejiya et al 2009), Anti-Microbial Activity (Bhatt...…”
Section: Syzygium Cuminimentioning
confidence: 99%
“…[6] Syzygium species exhibit antidiabetic, [7] antifungal, [8][9][10] anti-inflammatory, [11] antibacterial, [10,12] antioxidant, [10,13] antihyperlipidemic, [14] and growth inhibitory effects against oral pathogens. [15] The Syzygium species are also found to posses antihyperglycemic activity, [16] cytotoxic, [10,17] anti-angiogenic, [17] and anti-nociceptive activity. [18] To the best of our knowledge no study on the biological activity of Syzygium caryophyllatum is reported so far.…”
Section: Introductionmentioning
confidence: 99%